Immigration from Africa to the United States: key insights from recent research - Corra, Mamadi (Frontiers in Sociology, 2023)
Immigration from Africa to the United States has increased dramatically in the past three decades. This paper summarizes recent findings on the growth of African immigration to the United States in recent years. In doing so, it highlights shifting sociodemographic profiles of these “new African Americans” or “new Americans,” profiling the increasing diversity, yet also racialized portrait of this group. Key patterns of immigration shown include the changing racial and gender composition of immigrants, as well as rising immigration from a wider range of African countries. Some key theoretical and practical implications are outlined.